Sustainable Smart Cities and Smart Villages Research: Rethinking - Visvizi, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Over the last years, sophisticated policy making propositions for sustainable rural and urban development have been recorded. The smart village and smart city concepts promote a human-centric vision for a new era of technology-driven social innovation. This Special Issue offers a useful overview of the most recent developments in the frequently overlapping fields of smart city and smart village research. A variety of topics including well-being, happiness, security, open democracy, open government, smart education, smart innovation, and migration have been addressed in this Special Issue. They define the direction for future research in both domains. The organization of the relevant debate is aligned around three pillars: Section A: Sustainable Smart City and Smart Village Research: Foundations • Clustering Smart City Services: Perceptions, Expectations, and Responses • Smart City Development and Residents' Well-Being • Analysis of Social Networking Service Data for Smart Urban Planning Section B: Sustainable Smart City and Smart Village Research: Case Studies on Rethinking Security, Safety, Well-being, and Happiness • Exploring a Stakeholder-Based Urban Densification and Greening Agenda for Rotterdam Inner City-Accelerating the Transition to a Liveable Low Carbon City • The Impact of the Comprehensive Rural Village Development Program on Rural Sustainability in Korea • Analyzing the Level of Accessibility of Public Urban Green Spaces to Different Socially Vulnerable Groups of People • Consumers' Preference and Factors Influencing Offal Consumption in the Amathole District Eastern Cape, South Africa • Sustainable Tourism: A Hidden Theory of the Cinematic Image? A Theoretical and Visual Analysis of the Way of St. James • Future Development of Taiwan's Smart Cities from an Information Security Perspective • Towards a Smart and Sustainable City with the Involvement of Public Participation-The Case of Wroclaw Section C: Sustainable Smart City and Smart Village Research: Technical Issues • Detection and Localization of Water Leaks in Water Nets Supported by an ICT System with Artificial Intelligence Methods as a Way Forward for Smart Cities • A Study of the Public Landscape Order of Xinye Village • Spatio-Temporal Changes and Dependencies of Land Prices: A Case Study of the City of Olomouc • Geographical Assessment of Low-Carbon Transportation Modes: A Case Study from a Commuter University • Performance Analysis of a Polling-Based Access Control Combined with the Sleeping Schema in V2I VANETs for Smart Cities.